1996
DOI: 10.1037/0022-0167.43.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Drug use, violence, and victimization among White American, Mexican American, and American Indian dropouts, students with academic problems, and students in good academic standing.

Abstract: Problem-prone behaviors of White American, Mexican American, and American Indian high school dropouts, students in good academic standing, and students in poor academic standing were surveyed. Generally, dropouts were most involved with drugs, perpetration of violence, and victimization by violence, students in poor standing were the next most involved, and students in good standing were least involved. Ethnicity did not interact with academic status, suggesting that differences between dropouts and students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 26 publications
1
51
1
Order By: Relevance
“…Problem-prone behaviour and general deviancy theory describe adolescent dropping out and substance use as being two of a constellation of problem behaviours, co-varying with other deviant behaviours to which certain adolescents are prone (in BattinPearson et al 2000;Beauvais et al 1996;Fagan and Pabon 1990;Fergusson and Horwood 1997;Fergusson et al 1996;Kaplan and Liu 1994;Newcomb et al 2002;. Specifically, different forms of deviant behaviour co-vary because adolescents who hold non-conforming attitudes and values, and who attempt to establish their identities as independent and adult persons, are more likely to be engaged in a variety of non-conformist behaviours such as smoking, drug and alcohol use, and abandoning the student role (including dropping out of school) amongst others.…”
Section: Findings Related To Theoretical Framework/smentioning
confidence: 99%
“…Problem-prone behaviour and general deviancy theory describe adolescent dropping out and substance use as being two of a constellation of problem behaviours, co-varying with other deviant behaviours to which certain adolescents are prone (in BattinPearson et al 2000;Beauvais et al 1996;Fagan and Pabon 1990;Fergusson and Horwood 1997;Fergusson et al 1996;Kaplan and Liu 1994;Newcomb et al 2002;. Specifically, different forms of deviant behaviour co-vary because adolescents who hold non-conforming attitudes and values, and who attempt to establish their identities as independent and adult persons, are more likely to be engaged in a variety of non-conformist behaviours such as smoking, drug and alcohol use, and abandoning the student role (including dropping out of school) amongst others.…”
Section: Findings Related To Theoretical Framework/smentioning
confidence: 99%
“…6,13,14 Research has shown that inhalant use often occurs in conjunction with other risk behaviors and that higher rates of inhalant abuse occur among children who have poor grades or have dropped out of school compared with classmates who remain in good standing at school. 6,[13][14][15] Although inhalant abuse is more prevalent among 11 Similarly, most other studies have found rates of inhalant use by Hispanic youth to be the same as or lower than use by non-Hispanic white youth. [4][5][6][7][8]10,11 NSDUH data consistently show that rates of inhalant abuse by Asian American youth are among the lowest.…”
Section: Epidemiologymentioning
confidence: 99%
“…Others argue, however, that adolescent drug use is a normative aspect of development, and moderate use is not necessarily associated with negative outcomes (Shedler & Block, 1990). Associations between dropout and drug use suggest that these negative outcomes tend to co-occur across ethnic groups (Beauvais, Chavez, Oetting, Deffenbacher, & Cornell, 1996), and drug use has been shown to contribute to dropout risk among Hispanic youth (Fagan & Pabon, 1990). …”
mentioning
confidence: 99%